Grensverleggende beelden : Literaire transfer uit de Lage Landen naar Zuid-Europa - Gentile, Paola; Ross, Dolores; Gentile, Paola; Ross, Dolores (Gent Academia Press, 2020)
Crossing borders is a perilous undertaking, as this time of migrations and pandemics teaches us. Also for language-related cultural goods such as literary works, crossing those borders requires a lot of planning, strategic insights and a love for language and literature. After all, on their journey abroad, books bring with them other stories and cultural images, which in turn are filtered, if not manipulated, during the processes of selection and reception in the language of their destination. The study of this image (de)formation is therefore crucial in research into literary transfer. The authors of this collection respond to this by tracing the route of Dutch literature to Southern Europe and studying the image of Flanders and the Netherlands as expressed in translations through a combination of imagological and sociological translational findings. The conclusions in this collection show that the study of image formation in literary transfer can break through stereotypes and increase cultural awareness: crossing borders means pushing boundaries.
Grenzen overschrijden is een hachelijke onderneming, zoals deze tijd van migraties en pandemieën ons leert. Ook voor taalgebonden cultuurgoederen zoals literaire werken vergt het oversteken van die grenzen veel planning, strategische inzichten en een liefde voor taal en literatuur. Op hun reis naar het buitenland brengen boeken immers andere verhalen en culturele beelden mee, die op hun beurt ge lterd, zo niet gemanipuleerd, worden tijdens de processen van selectie en receptie in de taal van hun bestemming. De studie van die beeld(ver)vorming is daarom cruciaal in het onderzoek naar literaire transfer. De auteurs van deze bundel spelen hierop in door het parcours van de Nederlandstalige literatuur naar Zuid-Europa te traceren en via een combinatie van imagologische en vertaalsociologische bevindingen de beeldvorming van Vlaanderen en Nederland te bestuderen zoals die tot uiting komt in vertalingen. De conclusies in deze bundel tonen aan dat de studie van beeldvorming in literaire transfer stereotypen kan doorbreken en het culturele bewustzijn kan verhogen: grenzen overschrijden is grenzen verleggen.
Dutch
Keywords: Literature: history & criticism; literary transfer; reception; imagology; literaire transfer; receptie; imagologie